Impact of MgO Nanofluid Concentration on Thermal and Electrical Efficiency of PV/T Systems: A CFD and Experimental Study - Bryan Amrizha; Avita Ayu Permanasari (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2025)
This study investigates the effect of Magnesium Oxide (MgO) nanofluid concentration on the thermal and electrical efficiency of photovoltaic thermal (PV/T) systems using both experimental characterization and Computational Fluid Dynamics (CFD) simulation. Inlet flow rates (0.5–2.5 L/min) and MgO volume fractions (0.08%–0.4%) were varied. Experimental results confirm nanofluid stability for over 15 days at concentrations up to 0.2 vol%. CFD simulations using ANSYS Fluent reveal that the highest collector thermal efficiency of 69.1% is achieved at 0.2 vol% and 1.5 L/min, which is 16.7% higher than when using distilled water (DW) or ethylene glycol (EG) alone. The absorbed energy factor increases by 16.74%, while heat loss decreases by 52.2%. These findings highlight the significant performance gains attainable through optimized MgO nanofluid use in PV/T systems.